The Effectiveness of CBT Group Counseling with Self-Instruction Technique to Improve Students’ Self-Efficacy - Anggraini Masnur, Ade Dian; Wibowo, Mungin Eddy; Purwanto, Edy (Jurnal Bimbingan Konseling, 2022)
Self-efficacy is significant for students to improve motivation, self-confidence, and see any problems as a challenge. Therefore, school counselors are better to provide appropriate interventions to deal with self-efficacy issues. The present study attempted to examine the effectiveness of Cognitive Behavior Therapy group counseling with self-instruction technique to improve students’ self-efficacy. It used multiple group pretest posttest and involved 7 students in the experimental group. The subjects were selected using purposive sampling technique by considering their low self-efficacy. In the examination, the real data of the subjects were collected by distributing Adolescent Social Self-Efficacy Scale (S-EFF) instrument adopted into Indonesian with the alpha coefficient of .90. Findings showed that the Cognitive Behavior Therapy group counseling with self-instruction technique can effectively improve students’ self-efficacy. Finally, it recommends self-instruction technique to improve Junior High School students’ self-efficacy.